Exercise and Mitochondrial Dynamics: Keeping in Shape with ROS and AMPK - Adam J. Trewin; Brandon J. Berry; Andrew P. Wojtovich (MDPI AG, 2018)
Exercise is a robust stimulus for mitochondrial adaptations in skeletal muscle which consequently plays a central role in enhancing metabolic health. Despite this, the precise molecular events that underpin these beneficial effects remain elusive. In this review, we discuss molecular signals generated during exercise leading to altered mitochondrial morphology and dynamics. In particular, we focus on the interdependence between reactive oxygen species (ROS) and redox homeostasis, the sensing of cellular bioenergetic status via 5' adenosine monophosphate (AMP)-activated protein kinase (AMPK), and the regulation of mitochondrial fission and fusion. Precisely how exercise regulates the network of these responses and their effects on mitochondrial dynamics is not fully understood at present. We highlight the limitations that exist with the techniques currently available, and discuss novel molecular tools to potentially advance the fields of redox biology and mitochondrial bioenergetics. Ultimately, a greater understanding of these processes may lead to novel mitochondria-targeted therapeutic strategies to augment or mimic exercise in order to attenuate or reverse pathophysiology.